The Influence of Braille Flashcards as a Counseling Media on Various Depths of Dental Caries on the Knowledge of Children with Blind Disabilities Groups - Saluna Deynilisa; Windy Dea Angreini S; Syafiqah Nurul A; Bella Nurardiati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Imperfection of the sense of sight causes obstacles in taking action to maintain dental and oral hygiene. Provision of dental and oral health knowledge using a directed and structured plan in order to change bad habits and especially in dental and oral hygiene. One of them is by using Braille text. This study aims to determine the effect of the use of braille flashcards as a media for counseling about the depth of dental caries on the knowledge of children with disabilities in the blind group. The research method is pre-experimental with the one group pretest-posttest design approach which will be carried out in 2022. A sample of 20 people uses a purposive sampling technique. The average result of knowledge before counseling was 51.50 while the result after counseling was 86.75. In conclusion, there is an influence of braille flashcard media in increasing knowledge for the blind.